Photodisruptive Nd:YAG laser in the management of premacular subhyaloid hemorrhage - Çelebi, S; Kükner, AS (Wichtig Editore, 2001)
PURPOSE. Premacular subhyaloid hemorrhage is usually a benign condition that generally improves spontaneously and rarely causes visual loss. However, because the hemorrhage may cause permanent macular changes before it resolves, Nd:YAG laser posterior hyaloidotomy may be indicated in selected cases. This study investigated the effects of drainage of premacular subhyaloid hemorrhage into the vitreous with Nd:YAG laser treatment. METHODS. This study was conducted between February 1996 and March 1999. Six patients had a circumscribed premacular hemorrhage in one eye and were treated with the Nd:YAG laser to drain the blood into the vitreous cavity. The hemorrhage originated from Valsalva retinopathy (2 cases), proliferative diabetic retinopathy (2 cases), central retinal vein occlusion (1 case), and blunt ocular trauma (1 case). The size of the hemorrhage is expressed in disc diameters. RESULTS. The mean pretreatment hemorrhage measured 5.7 disc diameters (range 3.5-8.0). Visual acuity in all cases before laser treatment was hand movement. After laser treatment, the hemorrhage instantly drained into the vitreous cavity, resulting in rapid improvement of vision. Drainage was complete within one week and visual acuity improved dramatically. The mean follow-up was 26.3 months (range 7-42 months). No retinal damage or rebleeding occurred due to the laser treatment, and vitrectomy was not required in any eye. CONCLUSIONS. Nd:YAG laser posterior hyaloidotomy may be useful for draining a premacular hemorrhage into the vitreous cavity in selected cases. To establish this as a routine procedure, a randomized prospective study is needed to compare observation, primary vitrectomy, and Nd:YAG laser treatment.
Keywords: Nd : YAG laser; premacular subhyaloid hemorrhage; subinternal limiting membrane hemorrhage; Nd : YAG laser posterior hyaloidotomy